Platinum-Pemetrexed Chemotherapy for Recurrent Ovarian Cancer (ROC): A Single Center Experience. (26th November 2021) - Joel, Anjana; John, George; Daniel, Sherin; Thomas, Vinotha; Sebastian, Ajit; Ramireddy, Jeba Karunya; Chandramohan, Anuradha; John, Ajoy Oommen; Georgy, Josh Thomas; Chacko, Raju Titus; Yadav, Bijesh; Singh, Ashish
Abstract: In this retrospective analysis of 36 patients with recurrent ovarian cancer (ROC) treated with platinum pemetrexed doublet ± bevacizumab, the median age was 54.5 years (47–60) and 33 (91.7%) had serous histology. The overall response rate [ORR = complete (CR)+partial (PR) response] was 83.3%. At a median follow-up of 16 months, the median PFS was 13.8 months (95% CI: 10.849–20.580) and median OS 30.6 months, (95% CI: 21.46 months-NR). The incidence of Grade 3/4 anemia, thrombocytopenia, neutropenia and non-hematological toxicity was 19.4%, 3.9%, 16.6%, and 8.3%. Platinum pemetrexed chemotherapy in ROC is safe and effective treatment option.